Texts, readers, and positions: Developing a conceptual tool for teaching disciplinary reading in religious education. (June 2021) - Unstad, Lars; Fjørtoft, Henning
Abstract: Students' ability to learn in religious education (RE) depends on their ability to understand sources, such as textbooks, sacred scriptures, images and other forms of discourse. RE teachers therefore require practical tools to integrate reading and learning. This study explores how a conceptual tool designed for RE teachers to use in text-based learning activities can raise awareness of student positioning and enhance subject content knowledge in RE. Four Norwegian lower secondary classes and their RE teachers participated in a project focused on reading in RE. Using a design-based approach, we describe the development and use of a conceptual tool ( RE-spectare ) designed to raise awareness of positioning in RE. The tool affected teachers' approaches to texts. Students reported enhanced perceived subject relevance, increased disciplinary knowledge, and a heightened understanding of respect and tolerance. The tool can support teachers in developing strategies for inclusive teaching in RE. Highlights: Reading instruction in religious education requires awareness of positioning. Key positions include reading as insider-outsider and personal-professional. A conceptual tool helped teachers support students in understanding positions. Raising awareness of positioning can be a source of reading comprehension in RE.